Individual variation in the erythropoietic response to altitude training in elite junior swimmers - Friedmann, B.; Frese, F.; Menold, E.; Kauper, F.; Jost, J.; Bärtsch, P. (British Journal of Sports Medicine, 2005)
Objectives: Inter-individual variations in sea level performance after altitude training have been attributed, at least in part, to an inter-individual variability in hypoxia induced erythropoiesis. The aim of the present study was to examine whether the variability in the increase in total haemoglobin mass after training at moderate altitude could be predicted by the erythropoietin response after 4 h exposure to normobaric hypoxia at an ambient Po2 corresponding to the training altitude.